A exclusão da mulher do espaço sagrado: uma leitura a partir de Nm 12,1-16 - Reis, Floripes de Oliveira (2021)
This study seeks to demonstrate that in the tradition of the people of Israel and Judah, whose faith experiences are recorded in the Bible, there were women acting in the sacred space as both prophetesses and priestesses. In Num 12:1-16 there is a conflict between female and male priestly and prophetic forms, testifying that priesthood in Israel was not an exclusive service of men. Other biblical texts prove the existence of prophetesses, some of them with priestly functions as well. 2Kgs 23, when speaking of the goddess of Israel and Judah named Asherah worshipped in the shrines of Samaria and the temple in Jerusalem alongside YHWH, says that there were the sacred ladies of Asherah responsible for the worship and objects of the consort goddess of YHWH. To centralize religious and civil power in Jerusalem, Josiah promoted the destruction of the other gods with their priests. It is possible that when they destroyed the goddess Asherah her holy ladies were also murdered. But not everything was destroyed, because in the post-exilic period there was still conflict between the two forms of priesthood and just as in the Josianic reform, in the period of reorganization of the people around the temple, women were still being persecuted in their priestly practices(AU)